2022
DOI: 10.5194/acp-22-4705-2022
|View full text |Cite
|
Sign up to set email alerts
|

North China Plain as a hot spot of ozone pollution exacerbated by extreme high temperatures

Abstract: Abstract. A large population in China has been exposed to both severe ozone (O3) pollution and extreme heat under global warming. Here, the spatiotemporal characteristics of coupled extremes in surface O3 and heat (OPCs) over China are investigated using surface observations, a process-based chemical transport model (GEOS-Chem), and multi-model simulations from Phase 6 of the Coupled Model Intercomparison Project (CMIP6). North China Plain (NCP; 37–41∘ N; 114–120∘ E) is identified as a hot spot of OPCs, where … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…This clearly indicates that O 3 pollution is closely related to anthropogenic activities. In addition, the high O 3 concentration over NCP is also related to the high temperature extremes (Wang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This clearly indicates that O 3 pollution is closely related to anthropogenic activities. In addition, the high O 3 concentration over NCP is also related to the high temperature extremes (Wang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our simulations may underestimate surface O 3 concentrations under carbon neutrality scenario, because high air temperature can increase natural emissions (e.g. BVOC and soil NOx) (Lu et al 2021, Lei et al 2022 and accelerate photochemical reactions (Pyrgou et al 2018, Wang et al 2022 In this study, we only consider biogeochemical processes, including stomatal uptake and BVOC emissions to assess the impacts of terrestrial vegetation on surface O 3 , mainly because the feedback of vegetation on meteorology is not coupled in the GEOS-Chem model. Previous studies have showed that vegetation can decrease surface temperature and increase atmospheric relative humidity through transpiration (Mahmood et al 2014, Yu et al 2020.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…After COVID-19 lockdown period, the decreasing trend of NOx (59%) was much higher than that of TVOCs (41), which aggravated the rebound of O3 concentration. In addition, the increased P might exacerbate O3 pollution though T remained stable during COVID-19 period (Chen et al, 2019;Dong et al, 2020;Wang et al, 2022).…”
Section: Overview Of Observationsmentioning
confidence: 99%